2001
DOI: 10.3189/172756401781818266
|View full text |Cite
|
Sign up to set email alerts
|

Snow-ice accretion and snow-cover depletion on Antarctic first-year sea-ice floes

Abstract: Between austral late winter 1993 and austral autumn 1998, during five cruises aboard the research vessel Nathaniel B. Palmer, almost 300 m of core was obtained from first-year ice floes in the Ross, Amundsen and Bellingshausen Seas. Analysis of the texture, stratigraphy and stable-isotopic composition of the ice was used to assess the magnitude of the role of flooding and snow-ice formation at the base of the snowpack in the thickening of the ice cover and the thinning of the snow cover. Snow ice occurred in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 30 publications
10
120
2
Order By: Relevance
“…Seawater flooding is commonly observed in Southern Ocean pack ice characterized by high snow accumulation (up to 3 m) on relatively thin ice . As a result, the snow-ice interface often sinks below sea level, resulting in a negative ice freeboard (the elevation of the snow-ice interface relative to the local sea surface) and hydraulically forcing the infiltration of seawater and brine into snow, with slush and snow ice forming in the process (Jeffries et al, 1997(Jeffries et al, , 2001Haas et al, 2001;Maksym and Markus, 2008;Papadimitriou et al, 2009).…”
Section: Nutrient Sources and Exchangementioning
confidence: 99%
“…Seawater flooding is commonly observed in Southern Ocean pack ice characterized by high snow accumulation (up to 3 m) on relatively thin ice . As a result, the snow-ice interface often sinks below sea level, resulting in a negative ice freeboard (the elevation of the snow-ice interface relative to the local sea surface) and hydraulically forcing the infiltration of seawater and brine into snow, with slush and snow ice forming in the process (Jeffries et al, 1997(Jeffries et al, , 2001Haas et al, 2001;Maksym and Markus, 2008;Papadimitriou et al, 2009).…”
Section: Nutrient Sources and Exchangementioning
confidence: 99%
“…The resulting frozen mix of snow and ocean water, called snow ice, can be identified by various means in ice cores, from which we know that flooding occurs mainly in the Antarctic and contributes up to 25 % of ice production in certain areas Maksym and Jeffries, 2001). We base our understanding and treatment of flooding on the work of Jeffries (2000, 2001) and Jeffries et al (2001). To readers interested in flooding we recommend the PhD thesis of .…”
Section: Floodingmentioning
confidence: 99%
“…To provide an overview of the late autumn environment, a synopsis of conditions in the study area follows; detailed analyses of ice structure are reported in Jeffries et al (2001), and abundance and biomass of organisms of ice communities will be reported elsewhere (Garrison et al unpubl., Gibson et al unpubl. ) et al unpubl.).…”
Section: Discussionmentioning
confidence: 99%
“…Snow cover ranged from 0 to 36 cm. Frazil ice predominated north of 70°S, and congelation ice predominated south of 70°S (Jeffries et al 2001). Chl a concentrations were generally higher north of 70°S, reaching a maximum of >20 mg m -2 (Garrison et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation